Best practices for transradial approach in diagnostic angiography and intervention - Bertrand, Olivier F.; Rao, Sunil V. (Philadelphia, PA : Wolters Kluwer Health, 2015)
"This book will focus on the newer, more patient-friendly transradial approach to PCI. US physicians have been slow to move toward this approach, citing a lack of evidence confirming its superiority over the traditional femoral approach for PCI. Olivier Bertrand, a clinician in Canada,and instructor of international classes on the transradialapproach, will edit this book with a team of worldwide experts on this newer approach. Not only will this book contain "tips and tricks" for the procedures, but evidencefrom small studies and experienced facilities will be presented. We're at a tipping point in interventional cardiology - time is of the essence to bring out a practical book with the "seal of approval" of evidence"--Provided by publisher
Includes bibliographical references and index
1 13
Keywords: Angiocardiography; Cardiac catheterization; Cardiovascular system -- Diseases -- Diagnosis